Magnifying Endoscopic Features of Follicular Lymphoma Involving the Stomach: A Report of Two Cases - Masaya Iwamuro; Katsuyoshi Takata; Seiji Kawano; Nobuharu Fujii; Yoshiro Kawahara; Tadashi Yoshino; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
A 70-year-old woman presented with follicular lymphoma involving the stomach, duodenum, jejunum, bone, and lymph nodes. Esophagogastroduodenoscopy revealed multiple depressed lesions in the stomach. Examination with magnifying endoscopy showed branched abnormal vessels along with gastric pits, which were irregularly shaped but were preserved. The second case was a 45-year-old man diagnosed with stage II1 follicular lymphoma with duodenal, ileal, and colorectal involvement, as well as lymphadenopathy of the mesenteric lymph nodes. Esophagogastroduodenoscopy performed six years after the diagnosis revealed multiple erosions in the gastric body and angle. Magnifying endoscopic observation with narrow-band imaging showed that the gastric pits were only partially preserved and were destroyed in most of the stomach. Branched abnormal vessels were also seen. Pathological features were consistent with follicular lymphoma in both cases. The structural differences reported between the two cases appear to reflect distinct pathologies. Disappearance of gastric pits in the latter case seems to result from loss of epithelial cells, probably due to chronic inflammation. In both cases, branched abnormal vasculature was observed. These two cases suggest that magnified observations of abnormal branched microvasculature may facilitate endoscopic detection and recognition of the extent of gastric involvement in patients with follicular lymphoma.